Water Crisis Solutions In The Qur'an And Science - Rahmatina, Nada; Wardani, Wardani; Saputra, Riza (Jurnal Ilmiah Ilmu Ushuluddin, 2022)
Water is an essential need for human life and all living things. The community's high demand for water cannot be met because the water crisis is still happening today. A water crisis can be in terms of quantity and quality. This research aims to find the solutions in the Qur'anic and scientific perspective to solve the problem of water quantity and quality crisis in the Qur'anic perspective. This research uses thematic interpretation method (maudhû'î) with scientific interpretation approach. This research concludes water crisis solutions in terms of quantity and quality. The water quantity crisis solutions are divided into two major points. First, optimization of water management (Q.S. al-Ra'd/13: 17) which can be done through saving water (Q.S. al-Isrâ`/17: 26-27, Q.S. al-A'râf/7: 31) and making waterways or drainage (Q.S. Hûd/11: 44). Second, even water distribution (Q.S. al-Qamar/54: 28, Q.S. al-Baqarah/2: 60. Q.S. al-A'râf/7: 160) through the creation of water distribution reservoirs (Q.S. al-Zumar/39: 21) and prohibition of water privatization (Q.S. al-Hijr/15: 22). Meanwhile, the water quality crisis solutions are implied in the Qur'an and supported by scientific theory in five respects. First, reforestation (Q.S. al-An'âm/6: 99 and 141, Q.S. al Ra'd/13: 4, and Q.S. al-Nahl/16: 10-11). Second, watersheds conservation (Q.S. Hûd/11: 61). Third, controlling water pollution (Q.S. al-Ghâsyiyah/88: 12). Fourth, making biopore infiltration holes (Q.S. al-Rûm/30: 41, Q.S. Hûd/11: 37). Fifth, making rainwater harvesting (Q.S. al-Mu'minûn/23: 18).